TILGÆNGELIG AKUSTIK: Boligens lyd - Ryhl, Camilla (Tidsskriftet Antropologi, 2006)
The article describes and comments on implications of the absence of codes and regulations regarding the acoustic environment of housing design, in particular regulation of reverberation time. A Ph.D. dissertation, “A House for the Senses” from Royal Danish Academy of Arts, School of Architecture, 2003, forms this article’s basis, the evidence of which is described and documented with citations from the qualitative 1:1 spatial testing. Through empirical work with a group of people living with sensory disabilities, the article addresses, not only the needs and specific requirements for the individual disability, but also several human implications for acoustic perception in housing design. Spatial acoustics are sensed, not only through hearing, but also by one’s use of the sense of feeling, the kinaesthetic sense and balance as they pertain to sensory disabilities. Finally, the article suggests that acoustics serves as a significant element in architectural quality, as well as a measurable parameter of accessibility.